Implementation of strategic plans by Zimbabwean local authorities. - Manjobo, Lydia R. (Midlands State University, 2017)
This study aimed at assessing the implementation of strategic plans at Chitungwiza Municipality. Different stakeholders should be involved in strategy implementation and these should include the business community, trade unions and government ministries employees as well as council committees. The process of strategic implementation should ensure that meetings are scheduled to discuss and monitor execution; the municipality should ensure that it crafts an implementation plan. The research critically analyses challenges faced in implementing strategic plans. These challenges include lack of finance, politics, lack of motivation, resistance to change, lack of technology and lack of skilled manpower. The researcher used the case study research approach. Questionnaires and interviews were used as research instruments. Data was collected from a sample of 44 respondents and 34 respondents responded. From the findings it was noted that financial resources are a major barrier to strategy implementation. This is caused by the fact that residents are not paying their rates and the municipality has retrenched its bloated workforce which has seen the municipality parting away with huge sums of money. Resistance to change, lack of motivation, lack of stakeholder involvement, corruption are some of the challenges to strategy implementation. To overcome these challenges local authorities should ensure that communication is bottom up for internal stakeholders to be involved in implementation and for them to feel that they have a crucial role to play in implementation, there should be consultation meetings with the external stakeholders, the municipality should ensure that it has competent personnel and leadership who should be able to implement strategic plans. The balanced score card should also be used for effective strategy implementation and the Municipality should ensure that they train all the employees on strategic implementation and constantly hold meetings which are bottom up with their employees.